Railway crew scheduling in passenger transportation – optimization approach - Dziaduch, Izabela; Hanczar, Paweł (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2019)
In this paper, a railway crew scheduling problem is presented. The basic requirements related to the drivers’ working time, which should be considered in the presented topic, are characterized. The literature review of existing models for crew planning was also performed as well. In the main part of the article, the decision model, which will allow to plan a driver for a train, is defined. The article also contains an assessment of the possibility to use the presented model in the scheduling the work of rail crews in practice
Mathematical Economics, 2018, Nr 14 (21), s. 19-30
Keywords: driver scheduling; train transportation; exact model optimization